Perspective of Recent Advances in Acute Diarrhea - Bhattacharya, Sujit K. (IntechOpen, 2020)
Acute diarrheal diseases (ADD) are important causes of morbidity and mortality worldwide. ADD includes, among others, cholera, shigellosis, and rotavirus diarrhea. These diseases are known to cause sporadic epidemics. Cholera and shigellosis are known to even cause pandemics. The treatments of these two diseases have been simplified with the advent of oral rehydration therapy and effective antibiotics. However, development of drug resistance poses tremendous therapeutic challenges. This book includes chapters on new methods of classification of dehydration and this information will provide a better classification method of dehydration. Epilepsy and its association with acute diarrhea is a new area for research. Prevention of acute diarrhea in school children and treatment with herbal medicines are important areas to pursue further. The readers will find herein new concepts in diarrheal disease research and management.